¿Tarsis era Tarteso?: Lo que los textos bíblicos dicen (y no dicen) - Pereira Delgado, Álvaro (Hispania sacra, 2023)
Most of archeologists and historians place the biblical Tarshish in Tartessos, although there are dissenting voices which set it in Tarsus of Cilicia, or in other locations. Scholars have presented different evidence of archaeological, philological, epigraphic, and literary nature. In the present research, we will focus on the specific biblical proof about the identification between Tarshish and Tartessos. We will study the most relevant biblical passages (Genesis 10:4; 1 Kings 10:22, 22;49; 2 Chronicles 9:21, 20:36; Isaiah 23; Ezekiel 26-28; etc.). These texts have frequently been used as clear historical evidence. Nevertheless, these are compositions that were written many years after the narrated events. In addition, it is necessary to consider the literary and rhetorical dimension of these works, whose interests were more religious and ideological than historical and geographical. We will try to clarify what can be said and what cannot (or should not) be said about Tarshish, based on the biblical texts in which this toponym appears.